2016
DOI: 10.7589/2015-08-218
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies Virus and Brucella abortus from an Expanding Wild Pig (Sus scrofa) Population in Southern Oklahoma, USA

Abstract: Wild pigs (Sus scrofa) are causing increasing ecologic and economic damage at a global scale. Because wild pigs can carry !65 diseases that affect livestock, their widespread expansion threatens native wildlife and livestock. We screened wild pigs from south-central Oklahoma, US for antibodies against Brucella abortus, pseudorabies virus (PRV), and porcine reproductive and respiratory syndrome virus (PRRS). These pathogens were chosen because they are part of eradication programs in the US and could have large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Pseudorabies virus (PRV) was eradicated from domestic animals from the USA in 2004; however studies have found evidence of widespread circulation in feral swine (Gaskamp et al, 2016;Pedersen et al, 2013;Müller et al, 2011). While not a concern for human health, PRV transmission from feral swine to other species has been documented (Cramer et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudorabies virus (PRV) was eradicated from domestic animals from the USA in 2004; however studies have found evidence of widespread circulation in feral swine (Gaskamp et al, 2016;Pedersen et al, 2013;Müller et al, 2011). While not a concern for human health, PRV transmission from feral swine to other species has been documented (Cramer et al, 2011).…”
mentioning
confidence: 99%
“…While not a concern for human health, PRV transmission from feral swine to other species has been documented (Cramer et al, 2011). Molecular and serological surveys have found that feral swine are variably infected with porcine circovirus type 2 (PCV2), porcine reproductive and respiratory syndrome virus, vesicular stomatitis virus, Mycoplasma hyopneumoniae, Actinobacillus pleuropneumoniae, Lawsonia intracellularis, Salmonella, Streptococcus suis, Brucella suis and Brucella abortus (Gaskamp et al, 2016;McGregor et al, 2015;Baroch et al, 2015;Stephenson et al, 2015;Corn et al, 2009;Rodriguez et al, 2000). For PCV2, feral swine appear to be an important reservoir for genetic diversity (Franzo et al, 2015;Fabisiak et al, 2012).…”
mentioning
confidence: 99%
“…Wild pigs are host to 89 bacterial, viral, and parasitic diseases which can be transferred to livestock, wildlife, and humans 16,45,51 . Common diseases of concern transmitted from wild pigs to livestock are swine brucellosis, bovine tuberculosis, pseudorabies, and classical swine fever, while zoonotic diseases include brucellosis, Escherichia coli , salmonellosis, and leptospirosis 16,45,52,53 . Diseases at the livestock-wildlife interface pose challenges to wildlife managers and livestock producers, as well as towards quantitative risk analyses, as the disease status of wildlife populations and routes of transmission are often poorly understood 45,51 .…”
Section: Discussionmentioning
confidence: 99%
“…A primary concern surrounding wild pigs is disease transmission in the environment, especially at the livestock-wildlife interface (Miller et al 2013(Miller et al , 2017. The pathogens that wild pigs carry are also a public health concern, but are an even greater threat to commercial livestock operations (Gaskamp et al 2016). Wild pigs can harbor ≥65 infectious agents (i.e., bacterial, viral, parasitic) capable of causing disease in livestock, wildlife, and humans (Meng et al 2009, Cooper et al 2010, Haydett 2018, Preena et al 2020.…”
Section: Introductionmentioning
confidence: 99%